Comparing chloride ingress from seawater and NaCl solution in Portland cement mortar. (January 2019) - De Weerdt, K.; Lothenbach, B.; Geiker, M.R.
Abstract: This study investigates whether chloride ingress testing can be done using NaCl solution instead of seawater when assessing the performance of concrete in marine conditions. Seawater contains besides sodium and chlorine additional elements such as sulfur and magnesium, which can change the phase assemblage in the concrete and thereby affect chloride ingress. Mortar samples prepared with Portland cement were exposed to seawater or NaCl solution with a similar chloride concentration. After 180 days of exposure to seawater, only the outer 1 mm was enriched in sulfur and magnesium, which had only a limited impact on the chloride ingress. Leaching, observed in the outer 10–20 mm both for NaCl and for seawater exposure had a much stronger influence on the chloride ingress. Hence, chloride ingress in marine exposed concrete can be assessed using NaCl solutions. To mirror the leaching in field exposure, the volume of exposure solution needs to be high.